MERLOT learning exercises [electronic resource] - California State University System; MERLOT (Multimedia Educational Resource for Learning and Online Teaching).; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Long Beach, CA MERLOT, 2017)
Quoted from the homepage: Learning Exercises are projects, papers, or activities that can be part of the coursework for a class. Learning Exercises are linked to a learning material in MERLOT and may involve only that material, or it may involve other activities as well. In describing the Learning Exercises, the contributor describes the type of activity (i.e. in-class, homework assignment, individual assignment, group, etc.) as well as the time involved to complete it. The contributor also can identify learning objectives for the assignment as well as any assessment activities. Comments are observations of those who have either used the module or reviewed it. Comments submitted to MERLOT automatically become a "seed" for online discussions, permitting other MERLOT Members to comment on the comment. Members may also rate learning materials on a scale of 1-5, providing MERLOT users with the additional metric of a "crowd sourced" review for such materials. A Bookmark Collection is a gathering of MERLOT modules into a bookmark collection "folder" that any MERLOT Members can access. The owner of a Personal Collection can annotate each collection to explain its purpose.
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Aids and devices -- Open educational resources. .; Education, Higher -- Aids and devices -- Open educational resources. .